Primary mucinous eccrine carcinoma of the skin: a rare clinical tumor with many differential diagnoses - Scholz, Ina Maria; Hartschuh, Wolfgang (Journal der Deutschen Dermatologischen Gesellschaft, 2010)
Primary mucinous eccrine carcinoma of the skin is an extremely rare tumor most frequently occurring in the face or capillitium. It is felt to be an eccrine carcinoma, characterized by slow progress and unpredictable locally infiltrative growth. Therefore micrographic surgery is important to avoid local recurrence. It can be difficult to differentiate this carcinoma histologically from cutaneous metastases of breast or gastrointestinal tumors. Because of this, a primary staging in affected patients is essential.
Gesehen am 29.06.2023